IMPLEMENTASI METODE AGILE DEVELOPMENT DALAM PEMBUATAN WEB TK NEGERI PEMBINA KABAWETAN - Reza Anisa Tunjana; Harry Witriyono (PT. Hasba Edukasi Mandiri, 2025)
The rapid advancement of information technology requires educational institutions to adapt in order to improve service quality and information accessibility. In the context of developing a school information system, selecting the appropriate method is crucial to support efficiency and service quality. This study aims to apply the Agile Development method in the creation of the website for TK Negeri Pembina Kabawetan, located in Kepahiang Regency. The Agile method was chosen to ensure that the system development process remains adaptive to user needs and changes that may occur during the process. Data were collected through interviews with school representatives and documentation related to school administration and activities. The result of this research is an informative and functional website that is expected to facilitate school administration as well as improve information management and communication. The research findings include: 1.The developed information system can display and manage various essential information related to the school profile, including its history, vision and mission, teacher list, gallery, news, and a dedicated area for teaching staff. 2.The development process was carried out iteratively following the principles of Agile Development, involving users at every stage—from planning to testing—along with periodic evaluations and adjustments to be more responsive to user needs. 3.Testing results show that core features such as login authentication, profile data management, gallery, blog, and teacher management function properly and deliver outputs that meet expectations.These findings indicate that the developed system has successfully met the required functionalities and user needs.